2015
DOI: 10.1002/chem.201500314
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Addition to Alkenes: The Relation between Reactivity and Enthalpy of Hydrogenation: Regioselectivity is Determined by the Stability of the Two Conceivable Products

Abstract: Although electrophilic addition to alkenes has been well studied, some secrets still remain. Halogenations, hydrohalogenations, halohydrin formations, hydrations, epoxidations, other oxidations, carbene additions, and ozonolyses are investigated to elucidate the relation of alkene reactivities with their enthalpies of hydrogenation (ΔHhyd ). For addition of electrophiles to unconjugated hydrocarbon alkenes, ln(k) is a linear function of ΔHhyd , where k is the rate constant. Linear correlation coefficients are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[33] This rather perplexing correlation [34] suggests that attack of the electrophilic carbene by the more nucleophilic site of the alkene partner might be selectivity-determining,w hich happens to be the terminus if R 1 = R 2 = H, but the internal position if R 1 = R 2 = Me ("Markovnikovsr ule"). [35,36] Under this premise, 2a could evolve via a6 -endo-trig transition state H into the cyclopropane 3a by an outersphere process,whereas 2fis geometrically poised for metallacycle formation (I)and hence metathesis to furnish cycloalkene 11 a. [37] This tentative mechanistic interpretation is in accord with additional stoichiometric control experiments (Scheme 7), which indicate that the course of the reaction responds to the polarization of the alkene bond in ag ive substrate.S pecifically, 1a provides cyclopropane 3a,w hereas enyne 22 containing ad ifluoroolfinic site gave the metathesis product 11 a;since hydrogen and fluorine are isosteric, this divergent outcome implies that the product-determining step is (largely) governed by electronic rather than steric factors.…”
Section: Angewandte Chemiementioning
confidence: 78%
“…[33] This rather perplexing correlation [34] suggests that attack of the electrophilic carbene by the more nucleophilic site of the alkene partner might be selectivity-determining,w hich happens to be the terminus if R 1 = R 2 = H, but the internal position if R 1 = R 2 = Me ("Markovnikovsr ule"). [35,36] Under this premise, 2a could evolve via a6 -endo-trig transition state H into the cyclopropane 3a by an outersphere process,whereas 2fis geometrically poised for metallacycle formation (I)and hence metathesis to furnish cycloalkene 11 a. [37] This tentative mechanistic interpretation is in accord with additional stoichiometric control experiments (Scheme 7), which indicate that the course of the reaction responds to the polarization of the alkene bond in ag ive substrate.S pecifically, 1a provides cyclopropane 3a,w hereas enyne 22 containing ad ifluoroolfinic site gave the metathesis product 11 a;since hydrogen and fluorine are isosteric, this divergent outcome implies that the product-determining step is (largely) governed by electronic rather than steric factors.…”
Section: Angewandte Chemiementioning
confidence: 78%
“…As shown in the accompanying paper, 21 leads to a carbene of increased electrophilicity which one does not expect to bolster metathesis . This rather perplexing correlation suggests that attack of the electrophilic carbene by the more nucleophilic site of the alkene partner might be selectivity‐determining, which happens to be the terminus if R 1 =R 2 =H, but the internal position if R 1 =R 2 =Me (“Markovnikov's rule”) . Under this premise, 2 a could evolve via a 6‐ endo ‐ trig transition state H into the cyclopropane 3 a by an outersphere process, whereas 2 f is geometrically poised for metallacycle formation ( I ) and hence metathesis to furnish cycloalkene 11 a…”
Section: Methodsmentioning
confidence: 99%
“…This imaginary frequency is used to calculate a simple tunneling correction to the rate constant using the Wigner formula. 8 [34] The significance of this correction for the calculation at hand is found in the discussion section.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7] A recent study has shown a correlation between the rates of electrophilic addition and the hydrogenation energy of a large number of systems. [8] This correlation apparently breaks down for H 2 O and for highly polar media or under acid-catalysis. Anti-Markovnikov addition can be achieved by appropriate catalysts.…”
Section: Introductionmentioning
confidence: 99%